Optimization of endothelial growth factor receptor monoclonal antibody-gold nanorods photothermal therapy for laryngeal squamous cell carcinoma. Issue 2 (1st February 2022) - Hai, Yun; Wang, Hao; Qiu, Youyu; Huang, Renchao; Zhao, Liufang; Xu, Hongyang; Dong, Zichen; Zhang, Lu; Sun, Weidi; Zhang, Shiwen
ABSTRACT: It reported that heat generated by near-infrared laser irradiation of gold nanorods (AuNRs) effectively inhibited tumor cells, and the conjugate of epidermal growth factor receptor monoclonal antibody (EGFRmAb) and gold nanorods could selectively binded to the surface of cancer cell membrane expressing EGFR. However, there are few research reports on EGFRmAb-AuNRs in laryngeal squamous cell carcinoma. Therefore, our study aimed to investigate the photothermal effect of EGFRmAb modified AuNRs in inducing tumor cell death in an animal model of laryngeal squamous cell carcinoma. We showed that the conjugates of EGFRmAb and AuNRs selectively entered laryngeal squamous cell carcinoma cells. We analyzed the parameters of laser irradiation by controlling the near-infrared to optimize the condition and procedure of targeted treatment in nude mice treated with EGFRmAb and AuNRs. In addition, we examined the safety of the combined therapy. Test results showed that EGFRmAb-AuNRs inhibited the growth of Hep-2 and CNE-2 cells but not normal epithelial cells, and the semi-inhibitor concentration of EGFRmAb in Hep-2 and CNE-2 cells was 4 pmol/ml and 2 pmol/ml, respectively. AuNRs injected into the tumor and irradiated by near-infrared laser effectively inhibited tumor growth in nude mice without toxic effect in mice. We further confirmed that the apoptosis and necrosis rates of tumor cells in mice were highest under 3 W/cm 2 near-infrared laser irradiation and AuNRs minimum concentration of 280 μg/kg. In conclusion, we developed a new method of targeting EGFRmAb combined with AuNRs to achieve photothermal effect in the treatment of laryngeal squamous cell carcinoma. Graphical abstract: uf0001